Application of Load Balancing with the Nth Method on Multiple Gateway Internet Networks - Rasna Rasna; Ahmad Ashari (IJCCS (Indonesian Journal of Computing and Cybernetics Systems), 2019)
The Performance of a Network Is Necessary by the Office of the Special Jayapura Regent in matters related to networking. One of the technological problems to increase connections in the network is to use three ISPs and become microtik as a balanced load. Each ISP uses load sharing that can be divided evenly in each section. Wireless networks that are connected to distributed systems make load balancing techniques that can be received from a system. Load balancing can be applied to HTTP servers, proxies, databases, and gateways.     This research implements a proxy with load balancing method on an internet network that has three gateway lines through a router. Expected to be expected to be expected to be expected to load three ISP. The results of the research on the application of load balancing with the method on several internet gateways in the Jayapura District Regent Office is an inconsistency in bandwidth for each client before the implementation of the Nth method and using the Nth method with ten active clients can used when bandwidth on some clients is not much different and more evenly distributed than without load load balancing Nth.